Estado nutricional y nivel socioeconómico de los estudiantes de la Institución Educativa N°1712 Santa Rosa – Trujillo, octubre - noviembre del 2011 - Flores Castañeda, Angela Patricia (2012)
It made a cross-sectional and descriptive study with the goal to determine the nutritional status and socioeconomic level of students at the Santa Rosa 1712 Educational Institution Trujillo, October - November 2011. The population included 65 students. It was present the results of a comparison of weight and height of children with the new WHO (WHO/MGRS) international references. To expression and interpretation of indicators anthropometrics weight/ height, height /age and body mass index/age it used the computing Z scores, using for this program WHO Anthro 2005. For the evaluation of Z scores weight/ length and body mass index/age was classified with respect to standard deviation (SD) at: obese ≥ 2SD, overweight ≥ 1SD < 2, eutrophy > -1 SD < 1, thin ≤ -1 SD > -2 and acute malnutrition ≤ -2 SD. To Z score for the indicator height /age, the children were classified as high ≥ 2SD, normal > -1 SD < 1, low height ≤ -1 SD > -2 and chronic malnourished ≤ -2, then followed the joint analysis Z scores weight/ height, height /age and Z body mass index/age and it was verified in classification tables. To determine the socioeconomic level, a survey to the tutor for each child, with the coding point: lower under class-marginal 0 –22 points, upper lower class 23 – 43 points and upper middle class high 44 – 64 points. According to the results concluded that students mostly are in the normal nutritional status and a lower percentage malnutrition status, socioeconomic level upper lower class and not found relation between the nutritional status of children and socioeconomic level using the independence test chi-square variables, a significance level of 5%.